2016
DOI: 10.1021/acsenergylett.6b00417
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Free Carbon Nanotube Thermoelectrics with Improved Charge Carrier Transport and Power Factor

Abstract: Semiconducting single-walled carbon nanotubes (s-SWCNTs) have recently attracted attention for their promise as active components in a variety of optical and electronic applications, including thermoelectricity generation. Here we demonstrate that removing the wrapping polymer from the highly enriched s-SWCNT network leads to substantial improvements in charge carrier transport and thermoelectric power factor. These improvements arise primarily from an increase in charge carrier mobility within the s-SWCNT net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
96
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 46 publications
6
96
2
Order By: Relevance
“…They revealed that the Seebeck coefficient was increased as the purity of s-SWNT increased [29], which was also systematically studied by Piao et al [30]. For the s-SWNT sheets, it was demonstrated that Seebeck coefficient was further increased by optimizing the doping level chemically [14,16,31,32] or electrochemically [33][34][35] and, quite importantly, the higher purity of s-SWNT leads to a larger increase of Seebeck coefficient [29], thus the value reached to 2000 μV K −1 [14].…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…They revealed that the Seebeck coefficient was increased as the purity of s-SWNT increased [29], which was also systematically studied by Piao et al [30]. For the s-SWNT sheets, it was demonstrated that Seebeck coefficient was further increased by optimizing the doping level chemically [14,16,31,32] or electrochemically [33][34][35] and, quite importantly, the higher purity of s-SWNT leads to a larger increase of Seebeck coefficient [29], thus the value reached to 2000 μV K −1 [14].…”
Section: Introductionmentioning
confidence: 64%
“…On the other hand, the electrical conductivity of s-SWNT was much lower than that of m-SWNT, and the electrical conductivity decreased as the s-SWNTs purity increased [36]. Such a negative correlation between Seebeck coefficient and electrical conductivity cannot be ruled out even under changing the carrier density; namely, the increase of electrical conductivity of the s-SWNT network from 10 3 to 10 6 S m −1 by chemical doping resulted in the large decrease of the Seebeck coefficient [14,31,32]. Thus, the power factor (PF) of the s-SWNT network, defined as σS 2 , has a maximum value when the electrical conductivity is around 10 4 -10 5 S m −1 [14,31,32].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the ultimate case all nanotubes directly bridge the channel if it is short enough. [235,236] It is still unclear how much this resistance is influenced by the angle of overlap for two nanotubes, [236] by residual surfactant or wrapping polymer [250,251] and how it changes with doping/ gating. [81,110] The density of a nanotube network (see Section 2.4) is an important parameter for FETs.…”
Section: Charge Transportmentioning
confidence: 99%